A case of multiple organ failure due to massive bee stings with a rapid progress. A case of multiple organ failure due to massive bee stings with a rapid progress. - Yano, Rintaro; Miyoshi, Hiroshi; Yamashita, Kazunori; Sekino, Motohiro; Hara, Tetsuya (Japanese Journal of Reanimatology, 2020)
The patient was a 68-year-old male who was stung 70 or more times by wasps and was hospitalized at a local institution. Although the patient was initially lucid, respiratory and circulatory failure was observed 15 hours after being stung, and the patient was admitted into the intensive care unit (ICU) at our institution 24 hours after the trauma. In addition to renal disorder, elevated liver leakage enzymes and creatinine kinase were observed in the chemistry bloodwork. The patient was in a state of severe multiple organ failure, and underwent multidisciplinary treatment, including artificial respiratory management, circulatory management, and continuous hemodiafiltration; however, the patient's general condition did not improve, and the patient died 34 hours after the trauma. Wasp venom causes multiple organ failure from direct injuries to the target's body and may cause death by poisoning. It is therefore important not only to respond to the anaphylactic shock but also to administer multidisciplinary treatment at an early stage considering the complications associated with wasp poisoning when the number of stings is high.